Analisis Framing Pada KOMPAS.COM Dam REPUBLIKA Online Mengenai Pembakaran Bendera Berkalimat Tauhid - Nugraha Sugiarta; Duw Ruta (ArtComm, 2020)
Basically mass media is a place to construct reality. The construction of reality done by the media can result in the act of emphasizing or eliminating certain parts of the reality. The decision to do certain act is based on the perspective and the ideology adopted by each media. Therefore, among one media and the others there must be differences in packaging the news. The study aims to find out how the framing was done by Kompas.com and Republika Online in reporting the burning of a flag which has tawhid phrases written on it, in Garut. The method used to conduct the study is the qualitative research methods, with the constructionist paradigm, and used the Robert N. Entman’s framing analysis approach. Based on the results of the study, it can be concluded that Kompas.com views the issue of the burning of flag in Garut as an issue exploited by certain parties to lead public opinion by spreading flag burning video on the social media. While Republika Online defines the burned flag in garut is a HTI’s flag. Kompas.com appoints those who deployed flag burning issue as the cause of the problem, while Republika Online appoints the flag carrier as the cause of the problem. In connection to Kompas.com’s moral judgment, they highlight the fact that the viral flag burning video has been edited, while Republika Online mentions the flag carrier as an infiltrator. Both media suggest a legal settlement.